Pengaruh Tarif Pajak dan Probabilitas Audit terhadap Kepatuhan Pajak Penghasilan (Studi Eksperimen Laboratorium) - Kalangi, Lintje (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2014)
The objective of this research  is to analyze   the effect of tax rates, and the probability of audit on individual income tax compliance.This research is an explanatory  research, which done through  laboratory experiment, to explain the casual   relationships (causality)  between variables. Participants of  this experiment  consit of 30  students Master of Accounting and Accounting Professional  Program at Faculty of Economics, Sam Ratulangi University, Manado. The model analysis was of the research  using Normal Censored Tobit ).The results indicate that: (1)  tax rate has  positive effect on tax compliance behavior. (2) probability of audit has   positive effect on compliance tax and changes in probability  of audit level has different effect   on compliance tax.